Commercialization of Concrete and Construction Laboratory with ISO 17025:2017 Accreditation - Gunawan, Karmila Shieny; Bunga, Rianty Oshin Allo; Rahardjo, Jani (Proceedings International Conference on Education Innovation and Social Science, 2022)
Nowadays, internationally recognized test results of construction materials are critical for companies handling government projects in the construction sector. A university's Concrete and Construction Laboratory sees commercialization as a way to expand its capacity and usage to this potential market. The standardization strategy employed in this research is to implement and obtain ISO 17025:2017 accreditation. Preparation of required documents is carried out as the first step in preparing for accreditation. Preparation is done by identifying document requirements, identifying business processes, identifying document completeness using a checklist, analyzing document completeness, and generating conclusions. The results of the identification and analysis of the completeness of the documents using the checklist show that the documents that need to be made by this University’s Concrete and Construction Laboratory are as many as 70 documents and the four documents that have been owned need to be adjusted according to the requirements of ISO 17025:2017.